Associations between Place of Birth, Type of Attendant, and Small for Gestational Age Births among Pregnant non‐Hispanic Black Medicaid Recipients. (2nd February 2022) - Hansel, Shantoy; Kuyateh, Medjatu H.; Bello‐Ogunu, Faustina; Stranton, Derek T.; Hicks, Kayla; Huber, Larissa R. Brunner
Abstract : Introduction: Although non‐Hispanic Black women have increased risks of adverse birth outcomes compared with non‐Hispanic white women in the United States, there is a lack of research specifically focusing on non‐Hispanic Black women. Thus, this study's purpose was to evaluate whether place of birth and type of attendant used during labor is associated with having a newborn born small for gestational age (SGA) among non‐Hispanic Black Medicaid recipients. Methods: This study used 2017 Natality data from the National Vital Statistics System for non‐Hispanic Black women who used Medicaid as a source of payment (N = 322, 604). Type of attendant (ie, the medical professional who assisted during childbirth), place of birth (ie, setting where the woman gave birth), maternal factors, and SGA were obtained from birth certificates. We used multivariate logistic regression to investigate the association between place of birth, type of birth attendant, and newborns born SGA. Results: After adjustment, women who used a certified nurse‐midwife or other midwife as an attendant during labor had statistically significant decreased odds of having a neonate born SGA compared with those who had a physician as an attendant (odds ratio [OR], 0.69; 95% CI, 0.66‐0.71 and OR, 0.68; 95% CI, 0.55‐0.85, respectively). Those who gave birth in a birthing center or had planned home births also had statistically significant decreased odds of having a neonate born SGA (OR, 0.52; 95% CI, 0.38‐0.69 and OR, 0.37; 95% CI, 0.21‐0.66, respectively). However, those who had an unplanned home birth had twice the odds of having a neonate born SGA compared with those who gave birth at a hospital or clinic (OR, 2.00; 95% CI, 1.50‐2.64). Discussion: Given the racial disparity in adverse birth outcomes for non‐Hispanic Black women, the observed associations provide justification for future research to determine whether birthing location and birth attendant are related to SGA.